Defect initiation and accumulation kinetics in hard-coated WC-Co hardmetal under multi-axial loads at elevated temperature in a novel ball-in-cone test setup. (April 2022) - Walch, Lukas; Klünsner, Thomas; Krobath, Martin; Maier, Kathrin; Ecker, Werner; Pichler, Philip; Czettl, Christoph; Ebner, Reinhold
Abstract: In the metalworking industry, hard-coated WC-Co hardmetal tools are often used in machining applications. Generally, tool life is limited by pre-existing defects in the hardmetal substrate and defects that form during tool application. The complex, multi-axial loading situations and the high temperatures present in the cutting-edge area of machining tools are among the main reasons for the formation and growth of defects in operation. At present, there is a lack in experimental setups that can replicate these conditions. In the current work a novel material testing method is presented, which uses a spherical indenter and inclined specimen surfaces to apply multi-axial loads at 700 °C. The local stress state in the specimen was calculated using finite element simulation implementing an experimentally parameterized material model considering ratchetting and creep of the substrate material. Stresses ranging from mainly compressive to tensile-compressive were predicted. Initiation and accumulation kinetics of defects in the nm- to μm size regime were studied quantitatively. The comparison of stress calculations and damage development shows that positions with tensile-compressive stresses exhibited significantly higher defect formation rates than those with mainly compressive stresses. Highlights: Novel Ball-in-Cone test setup to induce significant multi-axial cyclic loads at high temperatures is introduced. Experimentally parameterized FE model considering creep and cyclic creep used to determine test setup load situation. Experimental results show defect initiation and accumulation kinetics in a hard-coated WC-Co substrate. Numerical results demonstrate stress range and stress ratio dependency of defect initiation kinetics. Load & damage situation as in milling cutting edges during milling are reproducible in laboratory experiment.